A case report of lymphoid intestitial pneumonia in common variable immunodeficiency: Oligoclonal expansion of effector lymphocytes with preferential cytomegalovirus-specific immune response and lymphoproliferative disease promotion. Issue 23 (June 2017) - Zdziarski, Przemyslaw; Gamian, Andrzej; Dworacki, Grzegorz
Abstract: Rationale: Lymphoid interstitial pneumonia (LIP) is a rare disease with lymphocytic infiltration of the alveolar interstitial and air spaces, sometimes classified as a clonal lymphoproliferative disease (LPD) with high prevalence in patients with immunodysregulation. Although association of mucosa-associated lymphoid tissue (MALT) lymphoma development with infectious agents has been well described, it is not so in the case of LIP. Attempts to demonstrate an infective cause by direct microbe detection have failed, but association with atypical specific immune response to opportunistic infectious agent has not been studied. Patient concerns and Diagnoses: We performed clinical, biochemical, and immunologic analysis of patients LIP that arises primarily from the common variable immune deficiency (CVID) with normal immunoglobulin class M (IgM) level and mild infectious course as a result of immunodysregulation. At the age of 13 multiple nodules, areas of consolidation were observed and LIP was confirmed by histological examination. The progression of the disease with massive splenomegaly (17→27 cm), lymphadenopathy soft tissue infiltration coincides with high standardized uptake value (SUV was 3.1–5.2), regulatory T cells decrease (CD4+25 high FoxP3+ level −0.02%, i.e., 8 cells per 100 μL), oligoclonal gammapathy: very high IgM (3340 mg/dL) and β2-microglobulin (18.8 mg/L) level observed 10 years later. Immune response polarization was observed in humoral and cellular compartment -Th and Tc-dependent: 10.8% of lymphocytes are CD8high+CMV pp65-pentamer positive cells (Epstein–Barr virus-specific not observed). Specific immune response polarization correlates with negative immunofixation, light chains κ / λ  = 2.84 and narrow, but non-monoclonal T cell receptor (TCR)/ B cell receptor (BCR) repertoire. Lessons: Taking everything into account, this case report shows that LIP is a consequence of immune-dysregulation in CVID, that is, Treg deficiency, narrow lymphocyte repertoire, and abnormal ability to respond to cytomegalovirus (CMV) antigens. It may be visualized by positron emission tomography (PET) and monitored by CMV-specific immune response, β2-microglobulin level, and IgM paraproteinaemia, but not by immunofixation and κ / λ ratio.